PERANCANGAN SISTEM DENGAN METODE WATERFALL PADA APOTEK XYZ - Sofiansyah Fadli; Sunardi Sunardi (LPPM STMIK Lombok, 2018)
Trade in the world the accuracy of the information is very needed, Especially information on the selling price , the price of basic supplies and sales of the rest of the administrative system accuracy in sales because the relationship between companies look to affect consumer as well as administrative systems sales in the company itself .An apothecary the goddess of a trading companies that move in the field of trade of various types of medication .The writer observes that the system the administration of the sale in pharmacies goddess is still done manually .During an apothecary rely more on this management in the price of memory , but not all the price of drugs could be remembered by employees so that employees often see a list price when there was a transaction .In addition to that employees have to see a list of supplies or cards supplies books to know the drug supplies. The research uses a method of structured approach that is used diagrams the current data (DAD) , entity relationship diagram (ERD), between advance design and implementation of , the making of the application of a system of the sale of the drug in the design a groove the system uses microsoft office visio 2007 as a medium to design a diagram a groove , a diagram the context , relation between entity and design page interface .On the implementation system using programming borland delphi 7 to design a display interface , and for data storage use mysqldatabase by using application sqlyog enterprise This system is the most effective pharmaceutical sales of data. By using a computerized system to ease the officer to use the data in accordance with the service.To reduce the level of the errors that does not want it is to be used as a medium for managing data to simplify and reduce the cost of the data.